The Routledge handbook of materials development for language teaching - Norton, Julie; Buchanan, Heather (London ; New York : Routledge, 2022)
"The Routledge Handbook of Materials Development for Language Teaching is the definitive resource for all working in this area of language and English language teaching. With 34 chapters authored by leading figures from around the world, the handbook provides an historical overview of the development of language teaching materials, critical discussion of core issues, and an assessment of future directions. The contributions represent a range of different international contexts, providing insightful, state-of-the-art coverage of the field. Structured in nine sections, the handbook covers: changes and developments in language teaching materials; controversial issues in materials development research and materials development ; materials for language learning and skills development ; materials evaluation and adaptation ; materials for specific contexts materials development and technology developing materials for publication ; professional development and materials writing. Demonstrating throughout the dynamic relationship between theory and practice, this accessible handbook is essential reading for researchers, scholars and students on MA programmes in ELT, TESOL and Applied Linguistics"--
Keywords: Language arts -- Curricula; Language and languages -- Study and teaching; Teaching -- Aids and devices; Applied linguistics; LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Linguistics